Practical pattern of surgical timing of childhood cataract in China: A cross-sectional database study. (February 2019) - Lin, Duoru; Liu, Zhenzhen; Chen, Jingjing; Lin, Zhuoling; Zhu, Yi; Chen, Chuan; Wu, Mingxing; Lin, Haotian; Chen, Weirong; Liu, Yizhi
Abstract: Background: The ideal surgical timings for cataract extraction (CE) and intraocular lens (IOL) implantation are vital for vision reconstruction in patients with childhood cataract (CC), yet they still remain controversial. We aimed to analyze the real-world practical pattern of surgical timings of CE and IOL implantations among a large number of Chinese CC patients. Materials and methods: This cross-sectional, database study included CC inpatients from the *** over a 10-year period (from January 2005 to December 2014). Binary logistic regression and multiple linear regression analyses were performed to identify the factors affecting the timings of CE and IOL implantation. Results: In the primary surgical stage, the mean ages of patients performed with CE (n = 839) and CE + IOL implantation (n = 1582) were 9.99 ± 18.21 months (5 th -95 th percentiles: 2–21) and 82.99 ± 52.99 months (5 th -95 th percentiles: 24–194), respectively. Surgical age, laterality, and axial length were identified as three factors (area under the curve [AUC]: 0.96, 95% CI: 0.94–0.97; Youden index: 0.86) affecting surgical procedure selection (CE or CE + IOL implantation) in the primary surgical stage. The time intervals between primary CE and secondary IOL implantation in bilateral (n = 311) and unilateral (n = 90) aphakia were 38.25 ± 16.84 months (5 th -95 th percentiles: 18–72) and 25.87 ± 10.56 months (5 th -95 th percentiles: 11–48), with significant difference (p < 0.001). Age at primary CE and laterality were identified as two factors affecting the time interval between primary CE and secondary IOL implantation in aphakic patients. Conclusions: The timings of CE and IOL implantation mainly varied with the age and laterality. This study may provide data-based clinical experience for ophthalmologists regarding CE and IOL implantation of CC in China and other countries with similar socioeconomic conditions. Highlights: The ideal timings for cataract extraction and intraocular lens implantation in cataractous children remain controversial. We presented the real-world surgical timings for the treatment of childhood cataracts in a large group of Chinese patients. The factors affecting the surgical timings of childhood cataracts were identified.